Perceived Peer Support, Autonomy and Self-Esteem Among Boarding School Students - Nurul Hidayah; Mohammad Sahari Nordin (Mahesa Research Center, 2020)
This study conducted to investigate perceived peer support and autonomy among boarding school students and its correlation with their self-esteem. Among 131 students from two selected boarding schools been the participant of this study. The researchers applied quantitative method in collecting data. The questionnaire adopted for this research was developed by Yueming Jia et al, (2009) and Way et al. (2007). The data showns that boarding school students perceived high level of peer support and autonomy. This due to amount of time they spend together in school hours and in the dormitory. They got the chances to to get involved in the decision-making process of the school like school regulation, teaching-learning activities and sports among classes. However, the study also found that there is no correlation between perceived peer support, autonomy and boarding school students’ self-esteem. This finding contradicted former studies which shows that social interaction with peer partly affect students’ mental health and self-esteem.